[11C]AZ10419369: A selective 5-HT1B receptor radioligand suitable for positron emission tomography (PET). Characterization in the primate brain - Pierson, M. Edward; Andersson, Jan; Nyberg, Svante; McCarthy, Dennis J.; Finnema, Sjoerd J.; Varnäs, Katarina; Takano, Akihiro; Karlsson, Per; Gulyás, Balázs; Medd, Amy M.; Lee, Chi-Ming; Powell, Mark E.; et al. (NeuroImage (Orlando, Fla.), 2008)
The 5-HT1B receptor has been implicated in several psychiatric disorders and is a potential pharmacological target in the treatment of depression. Here we report the synthesis of a novel PET radioligand, [11C]AZ10419369 (5-methyl-8-(4-methyl-piperazin-1-yl)-4-oxo-4H-chromene-2-carboxylic acid (4-morpholin-4-yl-phenyl)-amide), for in vivo visualization of 5-HT1B receptors in the brains of macaques and humans subjects. [11C]AZ10419369 was prepared by N-methylation of (8-(1-piperazinyl)-5-methylchrom-2-en-4-one-2-(4-morpholinophenyl) carboxamide, using carbon-11 methyl triflate. Regional brain uptake patterns of [11C]AZ10419369 were characterized by PET measurements in two macaques and a preliminary study in two human subjects. In addition, AZ10419369 was prepared in tritium labeled form for in vitro autoradiography studies in macaque brain tissue sections. The radiochemical purity of [11C]AZ10419369 was >99% and specific radioactivity was >3600 Ci/mmol. After iv injection of [11C]AZ10419369, 3-4% was in brain after 7.5 min. The regional brain distribution of radioactivity was similar in humans and macaques showing the highest uptake of radioactivity in the occipital cortex and the basal ganglia, in accord with autoradiographic studies performed using [3H]AZ10419369. Uptake was moderate in the temporal and frontal cortical regions, lower in the thalamus and lowest in the cerebellum. In macaques pre-treated with the selective 5-HT1B receptor antagonist, AR-A000002, binding was reduced in a dose-dependent manner, consistent with specific binding to 5-HT1B receptors. These data support [11C]AZ10419369 as a suitable radioligand for labeling 5-HT1B receptors in the primate brain. This radioligand may be useful in future studies evaluating drug-induced receptor occupancy and measurement of brain 5-HT1B receptor levels in patients with psychiatric disorders.